2022
DOI: 10.1523/jneurosci.1575-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Phrase Composition Revealed by Intracranial Recordings

Abstract: The ability to comprehend phrases is an essential integrative property of the brain. Here, we evaluate the neural processes that enable the transition from single-word processing to a minimal compositional scheme. Previous research has reported conflicting timing effects of composition, and disagreement persists with respect to inferior frontal and posterior temporal contributions. To address these issues, 19 patients (10 male, 9 female) implanted with penetrating depth or surface subdural intracranial electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 112 publications
6
47
0
Order By: Relevance
“…For example, analyzing the encoding weights for transformations (Fig. 5) revealed that posterior temporal areas assign higher weights to heads at earlier layers (positive values along PC1) with shorter look-back distance (negative values along PC2), consistent with previous work suggesting that posterior temporal areas perform early-stage syntactic (and lexico-semantic) processing (Hickok & Poeppel, 2000Flick & Pylkkänen, 2020;Murphy et al, 2022). Headwise correspondence in posterior temporal cortex was high for the ccomp and dobj dependencies (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…For example, analyzing the encoding weights for transformations (Fig. 5) revealed that posterior temporal areas assign higher weights to heads at earlier layers (positive values along PC1) with shorter look-back distance (negative values along PC2), consistent with previous work suggesting that posterior temporal areas perform early-stage syntactic (and lexico-semantic) processing (Hickok & Poeppel, 2000Flick & Pylkkänen, 2020;Murphy et al, 2022). Headwise correspondence in posterior temporal cortex was high for the ccomp and dobj dependencies (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, consistent with these findings, our results support the relationship between damage to the left PSAF and comprehension and repetition deficits in acute/subacute PSA. Given the importance of the temporal and parietal lobes for phrase comprehension and sentence syntactic processing [ 54 , 62 ] and its anatomical connection between these two areas, we inferred that the PSAF might play an important role in higher-order language functions (e.g., syntax), which was expected to be verified in future research.…”
Section: Discussionmentioning
confidence: 86%
“…In the DTI studies by Ivanova and colleagues [ 15 , 44 ], the FA value and volume measurements of the PSAF were significantly related to some lexical-semantic and syntactic language abilities, including auditory comprehension. Based on these previous reports and two recent studies that demonstrated that the pSTG, pMTG, and the posterior superior temporal sulcus (pSTS) were crucial for sentence comprehension and phrase comprehension [ 54 , 62 ], it is not novel to state that damage to the temporal cortical language areas and the left PSAF significantly affected auditory comprehension ability.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of pSTS was earliest (approximately 200 ms), and may pertain to composition-related demands or lexical search effort (Fig. 5–7), indexing greater engagement of compositional processing due to semantic narrowing demands (Flick and Pylkkänen, 2020; Matchin and Hickok, 2020), in particular given previous intracranial work implicating this region in basic semantic composition and lexicality (Murphy et al, 2022b). ATL engagement is in line with its apparent role in conceptual processing and entity-related (e.g., common object) representations (Thye et al, 2021; Turken and Dronkers, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Portions of fronto-temporal cortex were engaged for all aspects of language semantics, but become rapidly dedicated to certain processes at distinct times. Previous intracranial work has implicated pSTS in the initial construction of meaningful phrases, and IFS in the later evaluation of these phrases in the service of phrase-picture matching (Murphy et al, 2022b). Our results further highlight the role of pSTS-IFS in semantic composition demands, with early narrowing effects in pSTS (onset ∼ 250 ms) being followed by effects for all compositional processes in IFS (∼ 500 ms) (Fig.…”
Section: Discussionmentioning
confidence: 99%